Scales assessing L2 speaking anxiety: Development, validation, and application - Gao, Jie (Frontiers in Psychology, 2022)
Through featuring a historical review of the L2 speaking assessment scales applied in related studies, this paper targets at providing responses for the following three questions: (a) How are the scales assessing L2 speaking anxiety developed and adapted in related research? (b) What are the frequently adopted methods for validating speaking anxiety scales? (c) How is L2 speaking anxiety represented and interpreted with a dynamic approach? Based on analyzing the development process of frequently-used scales for assessing test anxiety, foreign language classroom anxiety, and speaking anxiety, the author classified the scales into three categories: test-based scales measuring speaking anxiety, classroom-based scales measuring anxiety, and activity-based scales measuring speaking anxiety. As for the scale validation methods, Classical Testing Theory (CTT) and Rasch measurement were introduced as two major statistical paradigms for guaranteeing the reliability of the scales. This paper also summarizes the emerging themes generalized from research focusing speaking anxiety assessment, where the dynamic approach is discussed as a guideline to interpret the relationship among anxiety, language performance, and other factors involved in language learning. This paper ends with highlighting possible directions for anxiety-related research in the future, where technology intervention and the "positivity ratio" might become new attempts for pedagogical design.